Difluorophosphoric Acid Generation and Crossover Reactions in LiNixCoyMnzO 2 Cathodes Operating at High Voltage - Jayawardana, Chamithri; Rodrigo, Nuwanthi D.; Rynearson, Leah; Lucht, Brett L. (Journal of the Electrochemical Society, 2022)
Cycling lithiated metal oxides to high potential (>4.5 V vs Li) is of significant interest for the next generation of lithium ion batteries as this significantly increases the capacity and energy of cells. However, cells cycled to high potential suffer from rapid capacity fade due to a combination of thickening of the anode solid electrolyte interphase (SEI) and impedance growth on the cathode. While transition metal catalysed degradation of the anode SEI has been widely proposed as a primary source of capacity loss, a related acid induced degradation of the anode SEI is proposed. A systematic investigation of LiNi0.5Co0.2Mn0.3O2, and LiNi0.8Co0.1Mn0.1O2cathodes cycled to 4.2 and 4.6 V has been conducted and the oxidative generation of the strong acid difluorophosphoric acid (F2PO2H) has been quantified by solution Nuclear Magnetic Resonance (NMR) spectroscopy. Ex-situ surface analysis of the electrodes with X-ray Photo Electron spectroscopy (XPS) suggests that the generation of F2PO2H correlates with a thickening of the anode SEI and an increase in the fluorophosphate content of the SEI. Changes to the LiNi0.8Co0.1Mn0.1O2surface for cells cycled to 4.6 V are also consistent with the generation of acidic species. There is good correlation between the concentration F2PO2H, anode SEI degradation and the capacity loss of the cells.